Phytoplankton phosphorus limitation in a North Atlantic coastal ecosystem not predicted by nutrient load - Trommer, Gabriele; Leynaert, Aude; Klein, Cecile; Naegelen, Aurore; Beker, Beatriz (Journal of Plankton Research, 2013)
Phytoplankton nutrient limitation patterns were investigated in an anthropogenically influenced coastal ecosystem with a high nutrient load. Weekly nutrient limitation bioassays, and water chemistry and stoichiometry measurements were performed in the Bay of Brest, France, from February to July 2011. Each limitation bioassay included phosphorus, nitrogen, silicate and all possible combined nutrient additions, and lasted over 72 h. Results showed that the phytoplankton community experienced a general P limitation from March to July. N limitation alone was observed only during 1 week in early March. Subsequently, all limitation bioassays revealed primary P limitation, indicated by significantly increased growth rates in all samples containing P additions. Besides P, Si was the second limiting nutrient for phytoplankton during 2 weeks at end of May to mid-June. Seston C:P ratios ranged between 198:1 and 749:1, and N:P ratios between 28:1 and 104:1. The highest effects on phytoplankton growth were reached with NPSi addition, suggesting synergistic macronutrient effects under single nutrient limitation. Our results demonstrate that dissolved nutrient ratios are not reliable in predicting actual phytoplankton nutrient limitation, since other processes and organisms strongly influence nutrient availability and resupply. The dominant P limitation emphasizes its importance for consideration in coastal water management.